The Imia Files - Dossier d'une crise: January 1996 - Janvier 1996 - --, -- (Études helléniques / Hellenic Studies, 2015)
Hellenic Ministry of Foreign Affairs Talking Points Concerning Unilateral Turkish Claims to the lmia Rocks La position de la Turquie Le différend relatif aux rochers de Kardak en mer Égée entre la Turquie et la Grèce (Ambassade de Turquie en France. Paris le 30 janvier 1996) European Parliament Adopted by a vole of 342 for, 21 against, 11 abstentions on February 15, 1996 on the provocative actions and contestation of sovereign rights by Turkey against a Member State of the Union